ANAL FİSSÜRLERDE MEDİKAL TEDAVİ - ERSAN, Yılmaz; YAVUZ, Nihat; ÇİÇEK, Yusuf and ERGÜNEY, Sabri and KUŞASLAN, Ramazan (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Fissure-in-ano or anal fissure is a linear longitudinal defect in the lining of the anal canal extending usually from the dentate line to the anal verge. Anal fissures affect all age groups, but predominantly occur in youngs and otherwise healthy adults. Although, most anal fissures are acute and relatively short-lived, resolving spontaneously, those persist and require intervention cause considerable morbidity. Recent researches to the physiology and pharmacology of the internal anal sphincter has elucidated the importance of this structure in health and disease. Current investigations consider raised resting pressure of internal sphincter and ischemia in posterior midline of anal canal as primary factors in the appearance and maintenance of this lesion. Much work has gone into the development of new pharmacological agents that can promote healing of anal fissures by production of a reversible chemical sphincterotomy. Recent innovations that have largely replaced surgery as first line treatment for anal fissure and the literature about these current treatment modalities has been reviewed. Conclusion.- The discovery of pharmacologic agents that effectively cause a chemical sphincterotomy and heal most fissures has led to approximately two thirds of patients avoiding surgery. Many of these drugs have a high rate of side effects in the short term. However, clinical trials have yet to establish the optimum doses, dose intervals and routes of administration for many of these drugs. Furthermore, it is uncertain whether this medical manipulation should be applied to all patients. Treatment of anal fissure must be individualized, depending on the clinical profile of patients. In particular, the occurrence of side effects limits their use and they are not always effective at healing fissures. However, despite these drawbacks, they remain excellent first line treatments of acute and chronic anal fissures. Furthermore, chemical sphincterotomy is particularly suitable in patients associated inflamatory bowel disease, syphilis, immunosupression including immunodeficiency virus (HIV) infection. When medical treatment fails or fissures recur, surgical treatment is indicated.